Effectiveness of internet-based CBT-I for the treatment of chronic subthreshold to moderate insomnia - Theppornpitak, Wongpitak; Hemrungrojn, Solaphat; Thienwiwatnukul, Krittapas; Muntham, Dittapol; Chirakalwasan, Naricha; Srisawart, Puntarik (Frontiers in Neurology, 2023)
Methods: An interventional study without control group was conducted between January and June 2022. Participants were adults aged 18 years old and older with subthreshold to moderate severity of chronic insomnia (ISI: insomnia severity index of 8-21) and had mean sleep efficiency < 85% from baseline sleep diaries. Baseline sleep characteristics were obtained from questionnaires and sleep diaries from Nitra application for 2 weeks. Eligible participants continued with Nitra application for 4 weeks during intervention period. Interventions including sleep restriction, stimulus control, cognitive restructuring, relaxation technique, and sleep hygiene education were implemented via pre-programmed Nitra application. Post-intervention sleep characteristics were also obtained from questionnaires and sleep diaries from Nitra application for another 1 week. Results: Total of 40 participants completed the study. All participants had baseline sleep efficiency less than 85% with the majority of the participants having a sleep onset insomnia problem (98%). For the primary outcome, sleep efficiency was significantly improved after using Nitra application (p < 0.001). Self-reported total sleep time, sleep onset latency, wake after sleep onset, early morning awakening, ISI, PSQI, and average subjective sleep quality were also significantly improved (p < 0.001 for all parameters except p = 0.017 for total sleep time and p = 0.018 for wake after sleep onset). Participants who had low baseline ISI and went to bed and woke up within 30 minutes of designated bedtime and wake up time recommended by Nitra application for ≥ 70% of all nights demonstrated increased chance of achieving normal sleep efficiency after using Nitra application. Conclusion: This first internet-based CBT-i in Thailand (Nitra application) effectively improved sleep efficiency and other sleep parameters in chronic subthreshold to moderate insomnia.